Characteristics of Dental Resin-Based Composites in Leukemia Saliva: An In Vitro Analysis - Alexandru Mester; Marioara Moldovan; Stanca Cuc; Ciprian Tomuleasa; Sergiu Pasca; Miuta Filip; Andra Piciu; Florin Onisor (Biomedicines, 2021)
Background: The aim was to analyze, in vitro, four resin based composite systems (RBCs) immersed in saliva of leukemia patients before starting chemotherapy regiments. Material and methods: Saliva was collected from 20 patients (4 healthy patients, 16 leukemia patients). Resin disks were made for each RBC and were immersed in the acute leukemia (acute lymphocytic (ALL), acute myeloid (AML)), chronic leukemia (chronic lymphocytic (CLL), chronic myeloid (CML)), Artificial saliva and Control environment, and maintained for seven days. At the end of the experiment, the characteristics and the effective response of saliva from the studied salivas’ on RBCs was assessed using water sorption, water solubility, residual monomer and scanning electron microscopy (SEM). Data analysis was performed and a p-value under 0.05 was considered statistically significant. Results: The behaviour of RBCs in different immersion environments varies according to the characteristics of the RBCs. RBCs with a higher filler ratio have a lower water sorption. The solubility is also deteriorated by the types of organic matrix and filler; the results of solubility being inversely proportional on the scale of negative values compared to sorption values. Chromatograms of residual monomers showed the highest amount of unreacted monomers in ALL and AML, and the Control and artificial saliva environments had the smallest residual monomer peaks. Because of the low number of differences between the experimental conditions, we further considered that there were no important statistical differences between experimental conditions and analysed them as a single group. Conclusion: The influence of saliva on RBCs depends on the type of leukemia; acute leukemia influenced the most RBCs by changing their properties compared to chronic leukemia.